Heavy metal contamination in Gulshan-Baridhara lake, Dhaka - Mohuya, Farzana Ahmed; Bhuiyan, Rejuan Hossain; Hoque, Sirajul (Dhaka University Journal of Biological Sciences, 2011)
Concentrations of cadmium (Cd), chromium (Cr), copper (Cu), nickel (Ni), and lead (Pb) in the pelagic water of Gulshan-Baridhara Lake were determined. The samples were collected from ten different spots in summer (April, 2007) and monsoon (August, 2007) seasons. The concentrations of Cd, Cr, Cu, Ni and Pb in the lake water varied from 0.068 - 0.091, 0.048 - 0.225, 0 - 6.135, 0 - 0.062 and 0.023 - 0.067 mg/l during the summer season, respec-tively. Mean values of the samples collected from mid points for Cd, Cr, Cu, Ni and Pb of ten stations in summer were 0.083, 0.100, 2.336, 0.074, and 0.046 mg/l, respectively. In monsoon the concentration of above mentioned heavy metals varied from 0.016 - 0.019 mg Cd/l, 0.005 - 0.035 mg Cr/l, 0.002 - 0.018 mg Cu/l, 0.007 - 0.159 mg Ni/l, and 0.052 - 0.151 mg Pb/l. Mean values of these heavy metals in monsoon were 0.018, 0.018, 0.011, 0.037 and 0.093, mg/l, respectively. The depletion factor was less than unity for Pb and exceptionally high for Cu. Finally the study revealed that among the heavy metals only Pb concentration exceeded the standard level during the monsoon, otherwise concentrations of all other four heavy metals (viz. Cd, Cr, Cu and Ni) exceeded the standard level of drinking-, fishing- and surface water as set up by WHO, GOB, USEPA, DOE and FWPCA, for the summer period. Key words: Status; Heavy metals; Contamination; Gulshan-Baridhara Lake DOI: http://dx.doi.org/10.3329/dujbs.v19i1.8944 DUJBS 2010; 19(1): 53-61